2015
DOI: 10.1210/en.2014-2027
|View full text |Cite
|
Sign up to set email alerts
|

Bisphenol A Exposure Disrupts Metabolic Health Across Multiple Generations in the Mouse

Abstract: Accumulating evidence has suggested that a suboptimal early life environment produces multigenerational developmental defects. A proposed mechanism is stable inheritance of DNA methylation. Here we show that maternal bisphenol A (BPA) exposure in C57BL/6 mice produces multigenerational metabolic phenotypes in their offspring. Using various methods including dual-energy X-ray absorptiometry analyses, glucose tolerance tests, and perifusion islet studies, we showed that exposure to 10 μg/kg/d and 10 mg/kg/d BPA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
131
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(140 citation statements)
references
References 33 publications
8
131
1
Order By: Relevance
“…The influence of several EDCs was demonstrated on the course of development of male gametes, sperm (Li et al 2011;Knez et al 2014) and female gametes, oocytes, as well as embryonic development of males and females (Mok-Lin et al 2010;Xiao et al 2011). Moreover, the effect of EDCs on the reproduction of adult individuals, including transgenerational inheritance, has been described (Susiarjo et al 2015;Ziv-Gal et al 2015). Therefore, reproductive functions represent crucial targets of the EDCs' negative effects.…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…The influence of several EDCs was demonstrated on the course of development of male gametes, sperm (Li et al 2011;Knez et al 2014) and female gametes, oocytes, as well as embryonic development of males and females (Mok-Lin et al 2010;Xiao et al 2011). Moreover, the effect of EDCs on the reproduction of adult individuals, including transgenerational inheritance, has been described (Susiarjo et al 2015;Ziv-Gal et al 2015). Therefore, reproductive functions represent crucial targets of the EDCs' negative effects.…”
Section: Endocrine Disruptorsmentioning
confidence: 99%
“…This was correlated with loss of imprinted monoallelic expression of Igf2 and Igf2 overexpression. A follow up study showed that these epigenetic changes coincide with increased body fat, insulin resistance and glucose intolerance only in adult male offspring [164]. In contrast to the study by Mackay and colleagues described above [161], females were seemingly unaffected.…”
Section: 2 Role Of Environmental Toxicants In Nutrient-regulated Omentioning
confidence: 99%
“…We identified five studies that examined the effects of in utero exposure to polycyclic aromatic hydrocarbons (PAHs) (42), bisphenol A (BPA) (35), dichlorodiphenyltrichloroethane (DDT) (34), methoxychlor (24), or the jet fuel JP-8 (36) on obesity phenotypes. Each of the studies provides preliminary evidence of the adipogenic potential of xenobiotic exposures to alter the epigenome in utero and contribute to later life obesity.…”
Section: Effect Of Environmental Pollutants On Obesitymentioning
confidence: 99%
“…Susiarjo et al (35) exposed dams to either NC, a low dose of BPA (10 μg/kg per day), or a high dose of BPA (10 mg/kg per day) from 2 weeks before conception through lactation. F1 offspring exposed to low or high BPA doses had higher body weight and fat mass, greater glucose intolerance, and altered insulin secretion compared with unexposed offspring.…”
Section: Effect Of Environmental Pollutants On Obesitymentioning
confidence: 99%